2016
DOI: 10.1021/acs.estlett.6b00382
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Host-Associated Fecal Markers on Child Hands, Household Soil, and Drinking Water in Rural Bangladeshi Households

Abstract: We evaluated whether provision and promotion of improved sanitation hardware (toilets and child feces management tools) reduced rotavirus and human fecal contamination of drinking water, child hands, and soil among rural Bangladeshi compounds enrolled in a cluster-randomized trial. We also measured host-associated genetic markers of ruminant and avian feces. We found evidence of widespread ruminant and avian fecal contamination in the compound environment; non-human fecal marker occurrence scaled with animal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(132 citation statements)
references
References 46 publications
5
125
2
Order By: Relevance
“…However, exposure to ruminant feces as a transmission pathway for enteric illness is underexplored in the WASH field. Similar results regarding the high prevalence of ruminant contamination has been reported for households in rural and urban/peri-urban informal settlements in Bangladesh [12] and Tanzania [10]. In addition, Barnes et al [59] showed an association between domestic animal presence/ownership and household drinking water contamination.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…However, exposure to ruminant feces as a transmission pathway for enteric illness is underexplored in the WASH field. Similar results regarding the high prevalence of ruminant contamination has been reported for households in rural and urban/peri-urban informal settlements in Bangladesh [12] and Tanzania [10]. In addition, Barnes et al [59] showed an association between domestic animal presence/ownership and household drinking water contamination.…”
Section: Discussionsupporting
confidence: 71%
“…Water quality indicators (i.e., MST molecular markers and FIB) were used in various analyses in binary (presence/absence) and continuous form (concentration of the molecular marker in the water sample). When continuous variables were used for FIB data, substitutions for NDs were necessary because the data were log 10 -transformed [12]. As such, NDs for FIB (E. coli and enterococci) were replaced with 0.5 CFU per 100mL water sample.…”
Section: Data Analysis-water Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…A laboratory supervisor received the environmental samples within 4 hours of collection and analyzed the samples for E. coli using the IDEXX-Quanti-tray ® 2000 technique with Colilert-24 media (IDEXX Laboratories, Westbrook, Seattle, WA) [31] to quantify the most probable number (MPN) of E. coli per unit of sample. E. coli is commonly used as an indicator of fecal contamination in water, food, and environmental samples [13,32,33]. We chose to use E. coli to allow for comparison with other studies.…”
Section: Laboratory Sample Processingmentioning
confidence: 99%